Experimental Induction of Cerebral Aneurysms by Developmental Low Copper Diet. Issue 5 (28th March 2016) - Jung, Keun-Hwa; Chu, Kon; Lee, Soon-Tae; Shin, Yong-Won; Lee, Keon-Joo; Park, Dong-Kyu; Yoo, Jung-Suk; Kim, Soyun; Kim, Manho; Lee, Sang Kun; Roh, Jae-Kyu
Abstract : Optimal models are needed to understand the pathophysiology of human cerebral aneurysms (CA). We investigated the development of experimental CA by decreasing the activity of lysyl oxidases by dietary copper deficiency from the time of gestation and then augmenting vascular stress by angiotensin II infusion in adulthood. Rats were fed copper-free, low-copper, or normal diets at different time periods from gestation to adulthood. The incidences of CAs were evaluated and autopsies performed to determine the coexistence of cardiovascular diseases. A copper-free diet from gestation was associated with high mortality rates (79.1%) resulting from rupture of ascending aorta aneurysms; a low-copper diet led to acceptable mortality rates (13.6%) and produced CAs and subarachnoid hemorrhage in 46.4% and 3.6% of animals, respectively. Higher proportions of CAs (up to 33.3%) in the rats primed for copper deficiency from gestation ruptured following angiotensin II infusion from adulthood. Gene expression array analyses of the CAs indicated that genes involving extracellular matrix and vascular remodeling were altered in this model. This model enables future research to understand the entire pathogenetic basis of CA development and rupture in association with systemic vasculopathies.